2017
DOI: 10.1021/acsmedchemlett.7b00315
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of AZD-2098 and AZD-1678, Two Potent and Bioavailable CCR4 Receptor Antagonists

Abstract: -(5-Bromo-3-methoxypyrazin-2-yl)-5-chlorothiophene-2-sulfonamide was identified as a hit in a CCR4 receptor antagonist high-throughput screen (HTS) of a subset of the AstraZeneca compound bank. As a hit with a lead-like profile, it was an excellent starting point for a CCR4 receptor antagonist program and enabled the rapid progression through the Lead Identification and Lead Optimization phases resulting in the discovery of two bioavailable CCR4 receptor antagonist candidate drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…A clinical trial of mogamulizumab in lung and esophageal cancer patients demonstrated that the antibody was well tolerated and led to efficient depletion of Tregs [ 98 ]. Allosteric antagonists that bind to the intracellular domain of CCR4 (class II antagonists) have been developed by pharmaceutical companies, including GlaxoSmithKline (GSK2239633) and AstraZeneca (AZD-1678, AZD-2098) [ 99 , 100 ]. RAPT pharmaceuticals have developed small-molecule inhibitors of CCR4, including FLX475 and RPT193.…”
Section: Chemokines Recruit Immunosuppressive Cells Into the Tmementioning
confidence: 99%
“…A clinical trial of mogamulizumab in lung and esophageal cancer patients demonstrated that the antibody was well tolerated and led to efficient depletion of Tregs [ 98 ]. Allosteric antagonists that bind to the intracellular domain of CCR4 (class II antagonists) have been developed by pharmaceutical companies, including GlaxoSmithKline (GSK2239633) and AstraZeneca (AZD-1678, AZD-2098) [ 99 , 100 ]. RAPT pharmaceuticals have developed small-molecule inhibitors of CCR4, including FLX475 and RPT193.…”
Section: Chemokines Recruit Immunosuppressive Cells Into the Tmementioning
confidence: 99%
“…The synthesized final compound and intermediates were screened for their CCR4 receptor inhibition activity. Compounds 366 (pIC 50 7.8) and 369 (pIC 50 8.6) were showed good potency against Human CCR4 receptor [126].…”
Section: Chlorine Containing Drugs As Miscellaneous Applicationsmentioning
confidence: 99%
“…To further investigate the role of CCR3 in this mechanism, the CCR3 inhibitor SB 297006 ( White et al., 2000 ) was added to normal FLS with and without CCR3 shRNA. The CCR4 inhibitor AZD 2098 ( Kindon et al., 2017 ) was employed to examine any potential signaling/cross talk through CCR4 ( Figure S2 ). The addition of AZD 2098 or SB 297006 had no effect on S100A12 expression in normal FLS in the absence of CCL22 regardless of CCR3 knockdown.…”
Section: Resultsmentioning
confidence: 99%